The Influence of Popular Culture’s Interpretation of Noah’s Ark upon Evangelical Reading and Interpretation - Hutchinson, Anna (Religions, 2024)
Whilst there is much published research looking at the use and/or interpretation of the Bible in popular culture, there has been little research investigating the impact of such cultural biblical engagement upon contemporary Christian Bible readers. Drawing upon focus group data, this paper thus explores the influence that the cultural history of Noah’s ark, particularly in popular culture, has upon the way evangelicals interpret. This paper shows that evangelical readers were influenced by the interpretations of the Noah story in the spheres of science, new atheism, children’s books and films, and this affected the conclusions they came to about the issue of historicity, morality and applicability. The paper closes with a reflection on why this phenomenon occurs and what hermeneutical benefits it might offer the reader by considering how God might be at work in the cultural depictions of Scripture and what they might offer interpretative practice.